GENDER AND EMPLOYABILITY IN HIGHER LEARNING INSTITUTIONS IN MALAYSIA: IMPLICATION FOR LEADERSHIP AND POLICY - Ghavifekr, Simin; Jani, Rohana Binti; Kenayathulla, Husaina Banu (PEOPLE: International Journal of Social Sciences, 2016)
Education is a key factor in human capital, social, economic, technological and political development of the society. Higher education institutions helps in producing high level manpower needed to attain speedy, purposeful and sustainable development in modern society. It provides students with skills and technical knowledge needed in coping with difficulties in the changing society. For higher learning institutions to perform their duties as expected, the need to employ skilled and competent experts in academic community is indispensable. This paper aims to overview the issues in regard to employability and gender in higher learning institutions. Moreover it tries to clarify the roles of policy makers and academic leaders in ensuring equal opportunity for all as a way of ensuring sustainable development. In order to achieve the goals of higher education globally, there is a need for re-orientation of people on gender disparity. Policy makers and academic leaders need to set a pace for others to follow by promulgating laws and guidelines that will ensure reasonable representation of skilled and competent personnel in academic community and eradicate gender segregation in employment process. Universities should be help and encourage students to develop their skills and capabilities. Concise effort must be made in supervising, guiding and evaluating students training program from time to time. This is to help students to thrive and compete favourable with their counterpart at workplace without facing the issues of gender and segregation.